How Does the Management of Subsidized Housing Loan Program Archives at The Palembang Government Bank Improve Efficiency and Public Services? - Rhianazala, Alzena; Putri, Aulia Utami (Kolaborasi : Jurnal Administrasi Publik, 2025)
This study examines the archive management of the Subsidized Home Ownership Credit Program at a state-owned bank branch in Palembang, focusing on operational challenges and their implications for public service efficiency. Using a qualitative approach, data was collected through observation, interviews, and documentation to explore factors influencing archive management, including document overload, inadequate storage facilities, and human resource competencies. The uniqueness of this study lies in the evaluation of the implementation of an innovative technology-based digital archive system and its impact on smart governance principles, as well as its contribution to enriching the literature on archive digitization in the public sector. The results indicate that optimizing archive management and developing human resource competencies can significantly improve administrative efficiency and service quality, providing empirical evidence to support innovation policies in public administration and more effective archive management.